Pengaruh Media Digital terhadap Motivasi Belajar di Era Teknologi Pendidikan - Esa Yulika Putri; Nadhratul Khairun Nisa; Gusmaneli, Gusmaneli (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The use of digital media in education has become a crucial requirement for improving the quality of learning in the technological era. Digital media encompasses various electronic-based platforms that help teachers deliver materials in a more innovative, interactive, and flexible manner. This study examines the benefits of digital media on student learning motivation, both intrinsic and extrinsic, as well as the challenges that arise in its implementation in schools. The study results indicate that digital media can increase student interest in learning, independence, and understanding through the presentation of visual, audio, and gamified content. Furthermore, digital media supports collaborative and contextual learning in line with 21st-century characteristics. However, limited access to technology, low digital literacy, and the potential for distraction are obstacles that still need to be addressed. The changing role of teachers as facilitators also requires continuous improvement in technological competency. Thus, appropriate strategies are needed to optimally implement digital media to increase motivation and learning effectiveness.